Work-integrated learning in Norway: Reviewing the field and future directions. - THON, ANDREAS; HAUGLID, BORGHILD BREKKE (International Journal of Work-Integrated Learning, 2025)
In Norwegian higher education, work-integrated learning (WIL) is an unfamiliar term. However, national policies and most higher education institutions emphasize the need for increased work relevance, or "arbeidslivsrelevans" (Norwegian term), across disciplines and programs. This study reviews existing literature to identify various WIL models in Norway involving students, educators, and industry partners, to better understand WIL within the Norwegian context. It finds that the majority of Norwegian WIL research focuses on placements, primarily in professional studies like nursing and teaching. There is limited research on WIL in pure science programs such as business, natural sciences and humanities. The study highlights the predominance of student-focused research and calls for more studies on placement and non-placement WIL models both from the perspectives of educators and from industry supervisors. This research enhances the understanding of WIL in the Norwegian context and reveals gaps in the literature regarding diverse perspectives in Norwegian WIL research.